Controversy over the medial border of lymph node dissection during CME/D3 surgery of right colon cancer - SUN Yueming, ZHANG Dongsheng (Waike lilun yu shijian, 2023)
Radical surgery is the most important treatment for colon cancer. The development and application of complete mesentery excision (CME)/D3 lymph node dissection has promoted the standardization of surgical techniques for colon cancer. Right colon cancer surgery is relatively complicated, and is a research hotspot currently. The issues involved the range of lymph node dissection, the range of bowel resection, and the method of bowel reconstruction. The medial border of lymph node dissection for right colon cancer is one of the controversies. The left side of the superior mesenteric vein is generally considered to be the medial border of CME/D3 dissection in right colon cancer surgery. However, with the in-depth development of related research, some scholars believed that the left side of the superior mesenteric artery should be used as the medial border for lymph node dissection. This approach is more consistent with the principle of CME, and can achieve complete lymph node dissection. However, its clinical significance still needs to be evaluated with further research. This article discusses the selection of medial border of lymph node dissection for right colon cancer, hoping to provide reference for clinical practice.